(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study examines the effects of retro materials combined with ergonomic designs on human psychology. While rapidly changing urbanization dynamics in Turkey increase longing for the past in individuals, retro designs stand out as tools that trigger feelings of nostalgia and belonging. The integration of retro-aesthetic elements with ergonomic principles provides physical comfort in individuals while also contributing to psychological well-being. The study analyzes the potential of retro designs to alleviate the stress and anxiety brought about by modern life by creating a sense of peace, serenity and belonging in individuals. This study aims to examine the effects of retro and ergonomic designs on different demographic groups, and the findings obtained are detailed in terms of the demographic characteristics, age, occupation, gender and living spaces of the participants. The study data were evaluated with the help of statistical analyses and the relationships of ergonomic designs with various parameters were analyzed comprehensively. The findings reveal that ergonomic and nostalgia-oriented designs create different effects on groups with different priorities. Differences in interest among participants based on their age, gender, occupational status and living spaces were discussed in detail. In this context, as a result of the evaluation of the data with frequency analysis, ANOVA, correlation and chi-square tests, significant differences were found between the effects of ergonomic designs and retro elements on certain demographic groups. As a result, it was seen that ergonomics-oriented designs contributed to the daily life quality and work efficiency of individuals, while retro designs were preferred more for nostalgic and aesthetic values. The findings of the study can guide designers in developing strategies suitable for different target groups.